2006
DOI: 10.1021/nl062228b
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline Branched Zinc Phosphide Nanostructures:  Synthesis, Properties, and Optoelectronic Devices

Abstract: Hierarchical tree-shaped nanostructures, nanobelts, and nanowires of Zn 3 P 2 were synthesized in a thermal assisted laser ablation process. All nanostructures are tetragonal phased Zn 3 P 2 with excellent crystallinity and are free from an oxidization layer according to electron microscopy and X-ray diffraction analyses. Optical measurement revealed a strong absorption from the ultraviolet to near-infrared regions. Optoelectronic devices fabricated using individual nanowires demonstrate a high sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 34 publications
(49 reference statements)
4
93
0
Order By: Relevance
“…This rapid response and recovery indicate that the CuO nanowires photodetecor is very sensitive to the IR illumination [30,31]. As a result, we could achieve a larger conductivity from the fabricated photodetector and thus a significantly larger photocurrent with fast response and recovery time less than 0.1 second.…”
Section: Figure 6 Enlarged View Of a Single On/off Cyclementioning
confidence: 95%
“…This rapid response and recovery indicate that the CuO nanowires photodetecor is very sensitive to the IR illumination [30,31]. As a result, we could achieve a larger conductivity from the fabricated photodetector and thus a significantly larger photocurrent with fast response and recovery time less than 0.1 second.…”
Section: Figure 6 Enlarged View Of a Single On/off Cyclementioning
confidence: 95%
“…TiO 2 is undoubtedly the best studied semiconductor photocatalyst so far. [1][2][3] However, owing to its wide bandgap ( % 3.2 eV), TiO 2 cannot be activated by visible light, which accounts for about 46 % of the total solar energy available. Therefore, for the full use of solar energy, it is desirable to develop new visible-lightresponsive semiconductor nanoheterostructure photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical structure results in a remarkable enhancement in their properties due to their large surface area and branch contributions [20][21][22]. For example, Wang et al [23] have reported the excellent field-emission properties of aluminum nitride nanorods with multi-tipped surfaces, and single-crystalline branched zinc phosphide nanostructures have displayed highly efficient spatially resolved photodetector characteristics [24].…”
Section: Introductionmentioning
confidence: 99%